Aeration optimisation of Biolgical Aerated Filters - Pearce, Peter A. (Cranfield University, School of Water Sciences, 1996)
Aeration costs account for a large proportion of the total running costs of biological aerated filters (BAFs) which are in themselves an energy intensive form of treatment process. Optimisation of oxygenation efficiency is therefore an obvious goal as small improvements in operating efficiency will yield significant savings in energy consumption. This paper will deal with the oxygen transfer characteristics of a downflow BAF using mineral media. Clean water and operational performance are compared over a range of hydraulic and organic loadings and a range of air flow rates. Alternative aeration devices and aeration procedures were also evaluated but will only be discussed in summary in this paper.